Human oncogenic viruses: an overview of protein biomarkers in viral cancers and their potential use in clinics - ARĞA, KAZIM YALÇIN (My University, 2022)
Introduction Although the idea that carcinogenesis might be caused by viruses was first voiced about 100 years ago, today\"s data disappointingly show that we have not made much progress in preventing and/or treating viral cancers in a century. According to recent studies, infections are responsible for approximately 13% of cancer development in the world. Today, it is accepted and proven by many authorities that Epstein-Barr virus (EBV), Hepatitis B virus (HBV), Hepatitis C virus (HCV), Human Herpesvirus 8 (HHV8), Human T-cell Lymphotropic virus 1 (HTLV1) and highly oncogenic Human Papillomaviruses (HPVs) cause or/and contribute to cancer development in humans. Areas covered Considering the insufficient prevention and/or treatment strategies for viral cancers, in this review we present the current knowledge on protein biomarkers of oncogenic viruses. In addition, we aimed to decipher their potential for clinical use by evaluating whether the proposed biomarkers are expressed in body fluids, are druggable, and act as tumor suppressors or oncoproteins. Expert opinion Consequently, we believe that this review will shed light on researchers and provide a guide to find remarkable solutions for the prevention and/or treatment of viral cancers.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Epstein-Barr virus; Hepatitis B and C virus; Human Herpesvirus 8; Human T-cell lymphotropic virus 1; Human Papillomaviruses; protein biomarkers; EPSTEIN-BARR-VIRUS; HEAT-SHOCK PROTEINS; HEPATOCELLULAR-CARCINOMA; HUMAN-PAPILLOMAVIRUS; ALPHA-FETOPROTEIN; PROGNOSTIC VALUE; KAPOSIS-SARCOMA; EXPRESSION; MARKER; DISCOVERY